Project management in the library workplace - Daugherty, Alice; Hines, Samantha (Samantha Schmehl) (Advances in library administration and organization,, 2018)
An important component of library administration and organization in the modern age is managing projects. Once the realm of technology and business gurus, formal project management tools, techniques and schemas have become more commonplace in libraries. Using formal project management components can help libraries achieve their desired outcomes with less stress for employees. However, there can be an entry barrier to project management, since the concepts are still somewhat out of the range of the usual library administration experience. This volume of Advances in Library Administration and Organization attempts to put project management into the toolboxes of library administrators through overviews of concepts, analyses of experiences, and forecasts for the use of project management within the profession.